Post-Caesarean Section Infection - Ahmed Mirghani, Omer (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 1 (2003), 2021)
Post-caesarean infection continues to be a major cause of maternal morbidity and mortality. Understanding the various aspects of this grave complication has improved our approach to its management and prevention. We review the present knowledge about post-caesarean infection regarding: incidence, risk factors, diagnosis, causative organisms, antibiotics and prophylaxis. We conclude that the incidence ranges between 5-85% depending on the population studied; the main risk factors are labour, ruptured membranes and repeated vaginal examinations, the diagnosis is mainly clinical, the infection is polymicrobial, the antibiotics of proven value are gentamycin/clindamycin, ureidopenicillins and third generation cephalosporins. Antibiotics prophylaxis is recommended in all women undergoing elective or non-elective caesarean section